FORMATION IN STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS OF THE NEEDS FOR REGULAR PHYSICAL CULTURE CLASSES - Yu.V. Subbota (Academy of Cognitive and Natural Sciences, 2009)
The article deals with the problem of forming of students of higher educational establishments necessity in regular physical training; to produce the results of awn sociological research; to perform the principal motives of forming of students of necessity in regular physical training.